Analysis of long‐term dry and wet conditions over Nigeria. (1st December 2016) - Oguntunde, Philip G.; Lischeid, Gunnar; Abiodun, Babatunde J.; Dietrich, Ottfried
ABSTRACT: Information on trends and changes in moisture conditions over a region can help policymakers to develop strategies for water resources and disaster risk management. In this study, the spatiotemporal variation of moisture indices and their annual trends in Nigeria were investigated. Thornthwaite moisture index (MI), the standardized precipitation index (SPI) and the standardized precipitation‐evapotranspiration index (SPEI) were computed for 1951–2014 period. Mann–Kendall trend and Sen's slope tests were used to examine the existence of temporal and spatial changes in these indices. MI decreased with increasing latitude and values ranged from −86 in the extreme north to +62 in the eastern part of the Niger Delta. A total of 73.4% of the landscape is under conditions where water supply is generally below the evaporative demand and only 26.6% of the area falls within wet sub‐humid and humid regimes. Significant downward trends were observed for all the moisture indices in most of the zones. In general, negative trends were observed in 98.2% of the landscape for MI, 96.7% for SPI and 98.2% for SPEI, showing drying tendencies over Nigeria. Between 40 and 50% of the land area is manifesting persistent shift towards aridity. Observed trends in MI is strongly correlated with that of SPI ( r  = 0.805) and SPEI ( r  = 0.715) and correlation of 0.886 was found between changes in SPI and SPEI. Rainfall generally showed higher and significant correlations with MI and slopes of all moisture indices. This information could help policymakers to develop appropriate coping and mitigation strategies for the most vulnerable areas.